Pochodzenie Słowian w świetle analiz genetycznych i genomicznych. podstawowe informacje o metodach i przegląd dotychczasowych wyników badań – z punktu widzenia archeologa - Jędrzejewska, Sylwia (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2022)
Bearing in mind the interdisciplinary nature of the origin of Slavs, in the process of reviewing the issue in relation with archaeology, the debate and the results of research carried out by representatives of other areas of science must be taken into consideration. The goal of this article is a review of the published results of an analysis of fossil and contemporary genetic material, coupled with discussing interpretation thereof in relation with the issue at hand. The work presents a selection of surveys which, according to the author, provide representatives of humanities with insight into the latest state of research. The presentation is preceded by introductory information about the examined material and the analysis methods as well as the conditioning factors. A methodological challenge was faced in the form of connecting data provided by geneticists and the findings from other disciplines, including archaeology, as indicated in the final part of the article.